Using the Method of Harmonic Distortion Analysis in Partial Discharge Assessment in Mineral Oil in a Non-Uniform Electric Field - Alper Aydogan; Fatih Atalar; Aysel Ersoy Yilmaz; Pawel Rozga (Energies, 2020)
In high-voltage equipment, it is vital to detect any failure in advance. To do this, a determination of the partial discharges occurring at different voltage types as well as at different electrode configurations is essential for observing the oil condition. In this study, an experimental setup consisting of a needle–semi-sphere electrode configuration immersed in mineral oil is prepared for laboratory experiment. In such a way, a non-uniform electric field is created and the leakage currents are monitored from the grounded electrode. A total of six different electrode configurations are analyzed during the tests by the use of hemispheres of different diameters as grounded electrodes and copper and steel pointed (medical) needle high-voltage electrodes. In the experiments, the partial discharges occurring at four different voltage levels between 5.4 and 10.8 kV are measured and recorded. The effect of the different electrode configurations and voltage levels on the harmonic distortion are noted and discussed. It is experimentally confirmed that it is possible to measure the leakage current caused by the partial discharges of the corona type in oil at the different metal points, creating high-voltage electrodes and different electric field distributions based on the proposed non-invasive measurement technique. The studies showed that there is a significant rise of even harmonic components in the leakage current during the increase in the partial discharge intensity with the 5th harmonic as dominant.